2007
DOI: 10.1158/0008-5472.can-06-2756
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tumor Growth and Metastasis by Depletion of Vesicular Sorting Protein Hrs: Its Regulatory Role on E-Cadherin and β-Catenin

Abstract: Abnormally high signals from receptor tyrosine kinases (RTK) are associated with carcinogenesis, and impaired deactivation of RTKs may also be a mechanism in cancer. Hepatocyte growth factor-regulated tyrosine kinase substrate (Hrs) is one of the master regulators that sort activated receptors toward lysosomes and shut down their signals. Hrs contains a ubiquitin-interacting motif and is involved in the endosomal sorting of monoubiquitinated membrane proteins, such as growth factor receptor and E-cadherin. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 50 publications
1
69
0
Order By: Relevance
“…Hgs, one of the master regulators that direct activated receptors toward lysosomes, has been shown to play an important role in the lysosomal targeting of E-cadherin (16). Hgs contains an ubiquitin-interacting motif and is involved in the endosomal sorting of ubiquitinated membrane proteins, such as growth factor receptors and E-cadherin (17)(18)(19)(20). Ubiquitinated Ecadherin is specifically trafficked to the lysosome for degradation (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hgs, one of the master regulators that direct activated receptors toward lysosomes, has been shown to play an important role in the lysosomal targeting of E-cadherin (16). Hgs contains an ubiquitin-interacting motif and is involved in the endosomal sorting of ubiquitinated membrane proteins, such as growth factor receptors and E-cadherin (17)(18)(19)(20). Ubiquitinated Ecadherin is specifically trafficked to the lysosome for degradation (16).…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitinated Ecadherin is specifically trafficked to the lysosome for degradation (16). Toyoshima and colleagues (20) revealed that Hgs depletion was associated with the upregulation of Ecadherin and reduced b-catenin signaling. The increased accumulation of E-cadherin observed in MARY-X spheroids and lymphovascular tumor emboli most likely results from impaired E-cadherin degradation in lysosomes mediated, in part, by decreased Hgs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, experiments addressed to analyze the candidate target genes expression were carried out in parathyroid tissues. Recently, HGS, which has been found highly expressed in a number of human cancers (Rayala et al 2006, Toyoshima et al 2007, has been reported as a target gene of the miR-296 inhibitory action in primary brain tumor endothelial cells (Würdinger et al 2008). Accordingly, both PaCs and adenomas characterized by low miR-296 expression levels showed HGS mRNA levels higher than those observed in PaN tissue.…”
Section: Endocrine-related Cancermentioning
confidence: 99%
“…MVB function has also been related to several kinds of cancer due to its role in the degradation of receptor tyrosine kinases and its involvement in cytokinesis. Accordingly, TSG101 has been found to be over-expressed in several cancers and Hrs over-expression is associated with malignancy (Toyoshima, et al 2007, Tu, et al 2011. Surprisingly, in other cases ESCRT loss-of-function, instead of overexpression, can lead to tumorigenesis.…”
Section: Endocytic Trafficking and Diseasementioning
confidence: 99%